Upaya Guru Akidah Akhlak Dalam Menciptakan Pembelajaran Yang Efektif Dan Menyenangkan Di Masa Pandemi Di MTs Mulia Securai - Siti Khomsiah Nasution, Kamaliah, Zainal Arifin Aka (Cybernetics: Journal Educational Research and Social Studies, 2022)
MTs Mulia Securai as one of the formal educational institutions that implements Distance Learning. From this condition, various efforts have been made by schools to be able to carry out effective and efficient learning. Teachers as educators are required to carry out teaching and learning activities through distance learning or online. This online learning itself requires creativity and innovation from educators, so that coaching, transfer of knowledge, and skills can run well. The objectives of this research are: To find out how the efforts of Akidah Akhlak teachers to create effective and fun learning during the Covid 19 pandemic at MTs Mulia Securai. This study uses a qualitative approach. The subjects of this study were the head of the madrasa, teachers of morals and students. Collecting data in this research using observation, interviews and documentation. The results of this study are the efforts of Akidah Akhlak teachers to create effective and fun learning during the Covid 19 pandemic is to make preparations before carrying out learning activities as in general such as lesson plans which are designed by utilizing all available learning potential and resources, the use of electronic media in the learning process. during the Covid-19 pandemic, Maximizing teaching skills during the Covid-19 pandemic, and building collaboration with parents of students.